2009
DOI: 10.2337/dc08-0944
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Physician Learning Intervention to Improve Safety and Quality of Diabetes Care: A Randomized Trial

Abstract: OBJECTIVE -To assess two physician learning interventions designed to improve safety and quality of diabetes care delivered by primary care physicians (PCPs).RESEARCH DESIGN AND METHODS -This group randomized clinical trial included 57 consenting PCPs and their 2,020 eligible adult patients with diabetes. Physicians were randomized to no intervention (group A), a simulated case-based physician learning intervention (group B), or the same simulated case-based learning intervention with physician opinion leader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…This is consistent with adult learning approaches, which suggest that physicians learn best in response to perceived relevant problems 53 . As a specific type of interactive technique, personalized feedback has been increasingly incorporated into successful education programs in many fields and has been shown to enhance learning 54,55 . Internetbased educational interventions provide the opportunity for interactivity and have grown rapidly in number across all health professions 56 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with adult learning approaches, which suggest that physicians learn best in response to perceived relevant problems 53 . As a specific type of interactive technique, personalized feedback has been increasingly incorporated into successful education programs in many fields and has been shown to enhance learning 54,55 . Internetbased educational interventions provide the opportunity for interactivity and have grown rapidly in number across all health professions 56 .…”
Section: Discussionmentioning
confidence: 99%
“…However, results of two previous published randomized trials using a prototype of the intervention showed effectiveness of this same simulation technology with practicing primary care providers by demonstrating improved glycemic control and reduced risky prescribing events in their real patients, without increasing costs. 41,42 The evaluation of the simulation technology observed in residents, combined with the outcomes observed in practicing health care professionals in previous studies, suggest that the simulated educational technology is well liked and can be effective for health care professionals with a range of clinical experience.…”
Section: Goal Setting 10mentioning
confidence: 87%
“…In a study published by O'Connor et al [14] 19 primary care physicians treated 3 simulated type 2 diabetes cases. The simulated patients (initial A1c 9.5% to 10.5%) represented 3 canonical types of patients that physicians commonly encounter in the clinic: (Case 1) compliant to treatment orders, requiring initiation/titration of oral medications; (Case 2) non-compliant due to undiagnosed depression, needing adjustment of oral and insulin medications doses; (Case 3) compliant, needing initiation/titration of insulin.…”
Section: Methodolgy 31 Datasetmentioning
confidence: 99%